Peningkatan Keaktifan dan Hasil Belajar Materi Keliling Dan Luas Bangun Datar Menggunakan Model PBL Siswa Kelas IV SDM Kemiri - Mahendri, Okti; Widiyono, Yuli; Suyoto, Suyoto (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to increase the activity and learning outcomes of Mathematics in the material of circumference and area of flat shapes using the Problem Based Learning method for fourth grade students of SD Muhammadiyah Kemiri. The results showed that there was an increase in student learning activity, namely the pre-cycle stage, the percentage of learning was only 37% in the first cycle, the first meeting was 50% while the second meeting was 58% so that the average activity in the first cycle was 52% in the active category and the second cycle of the first meeting by 79% while the second meeting was 91% so that the average activity of the first cycle was 85% in the very active category. Meanwhile, for student learning outcomes increased. This is evidenced by the percentage of mastery learning at the pre-cycle stage of 68%, in the first cycle an increase of 80%, an increase of 12% and an increase of 20% in the second cycle so that it reaches 100% in the very good category. So it can be concluded that the use of the problem based learning model in mathematics learning the material of perimeter and area of flat shapes can increase the activeness and learning outcomes of fourth grade students at SD Muhammadiyah Kemiri. Keywords: Keaktifan belajar, hasil belajar, matematika SD, model PBL